Detectability of cannabinoids in the serum samples of cannabis users: Indicators of recent cannabis use? A follow‐up study. Issue 9 (21st June 2021) - Krämer, Michael; Schäper, Martin; Dücker, Kristina; Philipsen, Alexandra; Losacker, Moritz; Dreimüller, Nadine; Engelmann, Jan; Madea, Burkhard; Hess, Cornelius
Abstract: Forensic toxicologists are frequently required to predict the time of last cannabis consumption. Several studies suggested the utility of minor cannabinoids as indicators of recent cannabis use. Because several factors influence blood cannabinoid concentrations, the interpretation of serum cannabinoid concentrations remains challenging. To assess the informative value of serum cannabinoid levels in cannabis users (in total N = 117 patients, including 56 patients who stated an exact time of last cannabis use within 24 h before blood sampling), the detectability of cannabinoids, namely, delta‐9‐tetrahydrocannabinol (delta‐9‐THC), 11‐hydroxy‐delta‐9‐THC, 11‐nor‐9‐carboxy‐delta‐9‐THC, cannabichromene (CBC), cannabidiol (CBD), cannabinol (CBN), cannabidivarin, tetrahydrocannabivarin, cannabigerol (CBG), cannabicyclol, delta‐8‐THC, tetrahydrocannabinolic acid A, cannabichromenic acid, cannabidiolic acid (CBDA), cannabigerolic acid, cannabicyclolic acid (CBLA), 11‐nor‐9‐carboxy‐THCV (THCVCOOH), and 11‐nor‐CBN‐9‐COOH, was investigated. Excluding CBDA and CBLA, all investigated cannabinoids were detected in at least one analyzed sample. The interval between cannabis consumption and sample collection (reported by the patients) was not correlated with cannabinoid concentrations. Minor cannabinoids tended to be more easily detected in samples obtained shortly after consumption. However, some samples tested positive for minor cannabinoids despite an interval of several hours or even days between consumption and sampling (according to patients' statements). For instance, CBC, CBG, THCVCOOH, CBD, and CBN in certain cases could be detected more than 24 h after the last consumption of cannabis. Thus, findings of minor cannabinoids should always be interpreted with caution. Abstract : To assess the informative value of serum cannabinoid levels in cannabis users ( N = 117 patients), the detectability of 18 cannabinoids (including metabolites) was investigated. The interval between cannabis consumption and sample collection (reported by the patients) was not correlated with cannabinoid concentrations. Minor cannabinoids tended to be more easily detected in samples obtained shortly after consumption. Conversely, some patients presented with detectable minor cannabinoid levels despite a long period between cannabis use and blood sampling.